2010
DOI: 10.1002/dvdy.22298
|View full text |Cite
|
Sign up to set email alerts
|

Early development of medaka Oryzias latipes muscles as revealed by transgenic approaches using embryonic and larval types of myosin heavy chain genes

Abstract: We cloned three full-length cDNAs encoding myosin heavy chains (MYHs) previously found to be expressed in embryos or larvae of medaka Oryzias latipes. Based on cDNA sequence information, the three medaka MYH genes, mMYH emb1 , mMYH L1 and mMYH L2 , were localized on the chromosomes. In vivo promoter assay using the gene encoding green or red fluorescent protein and linked to the 5 0 -flanking region of mMYH demonstrated that the transcripts of fast-type mMYH emb1 , first expressed in embryos but belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Medaka makes a particularly interesting subject because of the complete elimination of MYH14 from its genome. Although muscle fiber-type composition has not been well characterized in medaka, Ono et al [30] reported an MYH gene specifically expressed in slow muscle fibers at the horizontal myoseptum. Such MYH expression has never been reported in other teleost fish species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medaka makes a particularly interesting subject because of the complete elimination of MYH14 from its genome. Although muscle fiber-type composition has not been well characterized in medaka, Ono et al [30] reported an MYH gene specifically expressed in slow muscle fibers at the horizontal myoseptum. Such MYH expression has never been reported in other teleost fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sequence comparison analysis showed highly conserved 5′-flanking regions between torafugu MYH M5 and medaka miR-499 (see Figure 5A). The spatio-temporal expression of the major skeletal MYHs in teleost fish is regulated by small regions scattered throughout the 5′-flanking sequence [18,30,34,35]. Recently, Yeung et al [36] reported promoter activity in a 6.2-kb upstream sequence of mouse MYH14 that mimics endogenous MYH14 and miR-499 expression.…”
Section: Discussionmentioning
confidence: 99%
“…More diverse sarcomeric MYH s have been found in the fast muscle of teleosts, such as the common carp Cyprinus carpio [5-8], zebrafish Danio rerio [9-12], medaka Oryzias latipes [13-15] and torafugu Takifugu rubripes [16-19], at the genomic and transcriptional levels. In addition, genomic structural and syntenic analyses have revealed that at least 13 torafugu fast skeletal MYH s are distributed in 5 genomic regions, 3 of which contain multiple MYH s forming clusters A, B and C [18] (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genomic structural and syntenic analyses have revealed that at least 13 torafugu fast skeletal MYH s are distributed in 5 genomic regions, 3 of which contain multiple MYH s forming clusters A, B and C [18] (Figure S1). These clusters are also found in the green spotted pufferfish Tetraodon nigroviridis , zebrafish and medaka [12,15,18], implying that such genomic arrangement is conserved in teleosts. Interestingly, human fast skeletal MYH s form a single cluster, but their syntenic regions in torafugu, green spotted pufferfish and medaka are duplicated, although each locus contains a single MYH [18].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic structural analysis of torafugu revealed that fast-type MYHs in scaffold M743 (Fugu genome database Ver 3.0) form gene cluster C and are classified into an embryonic fast type (Ikeda et al, 2007) with its orthologous genes, all of which have also been reported to be expressed predominantly during embryonic and larval development in common carp (Nihei et al, 2006), medaka (Liang et al, 2007;Ono et al, 2006Ono et al, , 2010, and zebrafish Danio rerio (Berdougo et al, 2003;Bryson-Richardson et al, 2005;Wallace et al, 2005). The expression patterns of sarcomeric MYH M743-2 in early developmental stages of torafugu were analyzed by our laboratory members.…”
Section: Introductionmentioning
confidence: 99%